Flow cytometry in drug discovery and development - Litwin, Virginia M.; Marder, Philip (Hoboken, N.J. : Wiley)
"This book covers the unique application of flow cytometry in drug discovery and development. The first section includes two introductory chapters, one on flow cytometry and one on biomarkers, as well as a chapter on recent advances in flow cytometry. The second section focuses on the unique challenges and added benefits associated with the use of flow cytometry in the drug development process. The third section contains a single chapter presenting an in depth discussion of validation considerations and regulatory compliance issues associated with drug development"--Provided by publisher.